Tembotrione Half-Life in Soils with Different Attributes - SILVA,E.M.G. (2019)
ABSTRACT: Before recommending an herbicide, it is necessary to know its interactions with the soil attributes that will influence its sorption and half-life in the soil. This knowledge is an essential condition for minimizing any negative effects that may result from its application. However, due to the great diversity of soil and climate in Brazil, especially for products of recent use in the country, such as the herbicide tembotrione, this knowledge is often not available. This may be the main cause of occurrence of intoxication reports in crops carried out in succession to corn sprayed with this herbicide. In order to reduce possible impacts on successor crops and the contamination of surface and groundwater using the high-performance liquid chromatography, the tembotrione half-life was determined in soils with different attributes. The evaluated soils were a Red-Yellow Latosol with and without liming (Viçosa, MG), Red-Yellow Latosol (Rio Paranaíba, MG), Yellow Latosol (Sooretama, ES), and Red-Yellow Latosol with and without liming (Gurupi, TO). The results showed that liming might favor tembotrione degradation in the soil, as well as direct relationships between values of tembotrione half-life and contents of clay and soil organic matter. Tembotrione half-life in samples of Red-Yellow Latosol (without liming) collected in Viçosa and Rio Paranaíba, MG, was higher than 90 days, indicating carryover risks in successive crops to corn sprayed with tembotrione in these regions.